1992
DOI: 10.1007/bf00319020
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and functional response of predators to a long-term decline in mammalian prey at a semi-arid Neotropical site

Abstract: Occurrence and diet of ten carnivorous predators (four falconiforms, four owls, and two foxes), and population levels of their mammalian prey, were monitored over 45 months at a semi-arid site in north-central Chile. Early in this period, small mammals irrupted and then declined markedly to a density 7% of that at peak. All four falconiforms (Buteo polyosoma, Falco sparverius, Geranoaetus melanoleucus, Parabuteo unicinctus) and one owl (Tyto alba) responded numerically to the decline in mammalian prey by virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
9

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 32 publications
1
46
0
9
Order By: Relevance
“…Korpimäki and Norrdahl 1989;Hanski et al 1991;O'Donoghue et al 1997O'Donoghue et al , 1998Nielsen 1999;Tornberg et al 2005;Gilg et al 2006). The traditional association of predation ecologists with higher latitudes has led to a virtual lack of knowledge on complex natural systems such as those in Mediterranean and tropical climates (JacksiT et al 1992;Valkama et al 2005), which contain the largest number of predators, prey--with their dynamics not following (marked) cycles--and interactions between them. This is a major concern because stability (non-cyclical behaviour) imposes obvious restrictions to the amplitude of predator responses.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…Korpimäki and Norrdahl 1989;Hanski et al 1991;O'Donoghue et al 1997O'Donoghue et al , 1998Nielsen 1999;Tornberg et al 2005;Gilg et al 2006). The traditional association of predation ecologists with higher latitudes has led to a virtual lack of knowledge on complex natural systems such as those in Mediterranean and tropical climates (JacksiT et al 1992;Valkama et al 2005), which contain the largest number of predators, prey--with their dynamics not following (marked) cycles--and interactions between them. This is a major concern because stability (non-cyclical behaviour) imposes obvious restrictions to the amplitude of predator responses.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…Burrowing owls are well suited for studying the control of migratory tendency. Unlike many other owl species, the burrowing owl is a generalist predator that does not exhibit irruptive movements (Jaksic et al 1992;Haug et al 1993;Poulin et al 2001), and breeding populations throughout western North America vary in the proportion of individuals that migrate south during winter (Haug et al 1993;Klute et al 2003;Conway et al 2006). Populations in southern Arizona appear to be partially migratory: some individuals disappear during winter while others are present year round Conway and Ogonowski 2005;Ogonowski and Conway 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies of Chilean mediterranean-type ecosystems suggested a major role of predation on small mammals (e.g., Jaksic et al 1979Jaksic et al , 1981Jaksic et al , 1992Jaksic et al , 1993, and a major effect of small mammal herbivores on plants (Fuentes and Le Boulengé 1977;Jaksic and Fuentes 1980;Fuentes et al 1983Fuentes et al , 1984. However, few longterm field experiments have been conducted in the temperate Neotropics, and such studies are necessary to assess the generality of patterns largely derived from studies conducted in the Northern Hemisphere (Davidson et al 1985;Brown et al 1986;Brown and Heske 1990;Samson et al 1992;Heske et al 1993Heske et al , 1994.…”
Section: Introductionmentioning
confidence: 95%